Towards a more transparent HTA process in Poland: new Polish HTA methodological guidelines. Issue 1 (1st January 2017) - Lach, Krzysztof; Dziwisz, Michal; Rémuzat, Cécile; Toumi, Mondher
ABSTRACT: Introduction : Health technology assessment (HTA) in Poland supports reimbursement decisions via the Polish HTA Agency (AOTMiT), whose guidelines were updated in 2016. Methods : We identified key changes introduced by the update and, before guideline publication, analysed discrepancies between AOTMiT assessments and the submitting marketing authorisation holders (MAHs) to elucidate the context of the update. We compared the clarity and detail of the new guidelines versus those of the UK's National Institute for Health and Care Excellence (NICE). Results : The update specified more precise requirements for items such as indirect comparison or input data for economic modelling. Agency–MAH discrepancies relating to the subjects of the HTA update were found in 14.6% of published documents. The new Polish HTA guidelines were as clear and detailed as NICE's on topics such as assessing quality of evidence and economic modelling, but were less informative when describing (for example) pairwise meta-analysis. Conclusions : The Polish HTA guidelines update demonstrates lessons learned from internal and external experiences. The new guidelines adhere more closely to UK HTA standards, being clearer and more informative. While the update is expected to reduce Agency–MAH discrepancies, there remain areas for development, such as providing templates to aid HTA submissions.